Kinetic characterization, optimum conditions for catalysis and substrate preference of secretory phospholipase A2 from Glycine max in model membrane systems - Mariani, Maria Elisa (2015)
Two secretory phospholipase A2 (sPLA2s) from Glycine max, GmsPLA2-IXA-1 and GmsPLA2-XIB-2, have been purified as recombinant proteins and the activity was evaluated in order to obtain the optimum conditions for catalysis using mixed micelles and lipid monolayers as substrate. Both sPLA2s showed a maximum enzyme activity at pH 7 and a requirement of Ca2þ in the micromolar range. These parameters were similar to those found for animal sPLA2s but a surprising optimum temperature for catalysis at 60 C was observed. The effect of negative interfacial charges on the hydrolysis of organized substrates was evaluated through initial rate measurements using short chain phospholipids with different head groups. The enzymes showed subtle differences in the specificity for phospholipids with different head groups (DLPC, DLPG, DLPE, DLPA) in presence or absence of NaCl. Both recombinant enzymes showed lower activity toward anionic phospholipids and a preference for the zwitterionic ones. The values of the apparent kinetic parameters (Vmax and KM) demonstrated that these enzymes have more affinity for phosphatidylcholine compared with phosphatidylglycerol, in contrast with the results observed for pancreatic sPLA2. A hopping mode of catalysis was proposed for the action of these sPLA2 on mixed phospholipid/triton micelles. On the other hand, Langmuir-monolayers assays indicated an optimum lateral surface pressure for activity in between 13 and 16 mN/m for both recombinant enzymes.